An Empirical Examination of Keynesian and Wagner's Hypotheses in Emerging Asian Countries - Md Shahjahan (The Jahangirnagar Review, 2025)
Economists have paid much attention to the nexus between government expenditure and economic growth for decades. The research's foremost concern is verifying the Keynesian and Wagner's hypotheses in emerging Asian countries from 2005 to 2022. A univariate analysis is conducted to confirm the causal relationship and measure whether panel series are integrated in the same order. A causal relationship exists in emerging Asian countries. The estimation results observe the Keynesian proposition in Bangladesh and the Philippines and Wagner's proposition in China, Singapore, and Thailand. Also, the finding directs the presence of Keynesian and Wagner's Hypotheses in India, Indonesia, the Korean Republic, and Malaysia. Moreover, economic growth/government expenditure positively impacts government expenditure/ economic growth through impulse response functions that explain the short-term and long-term status.